Beyond Passion and Perseverance: Review and Future Research Initiatives on the Science of Grit - Datu, Jesus Alfonso D. (Frontiers in Psychology, 2021)
Grit, which is originally conceptualized as passion and perseverance for long-term goals, has been associated with optimal performance. Although previous meta-analytic and systematic reviews summarized how grit relates to performance outcomes, they possess considerable shortcomings, such as (a) absence of summary on the association of grit with well-being outcomes; (b) absence of discussion on social, psychological, and emotional mechanisms linking grit to well-being; and (c) lack of elaboration on how alternative models can resolve fundamental problems in the grit construct. This integrative review provides a comprehensive summary on the link of grit to performance and well-being outcomes. Importantly, it elaborates how alternative models can potentially address flaws in the existing grit theory. Future research directions are discussed on how to move forward the science of grit.